استخدام المدخل السياقي في تعليم اللغة العربية في المدرسة المتوسطة المعارف الاسلامية 01 سنجاساري مالانج - Maulidiya, Devi Mufidatul (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
ABSTRACT Learning Arabic in school is not strange. However, many students do not believe that Arabic is a difficult language. Students do not have the ability to apply Arabic in everyday life. It is feared that students are not ready to accept global challenges and developments in scientific and technological civilization. The need for a contextual approach to learning relies on the fact that most students are unable to make connections between what they learn and how it is used in real life. The objectives of this research is knowing the use of the contextual approach in teaching Arabic in the Islamic Junior High School Al Maarif 01 Singosari Malang. The research approach used by the researcher in this research is the qualitative approach and the descriptive approach. The data collection method used by the researcher in this research is observation, interview, and documentation. The technique used to check and validate the data is triangulation. The research population in this research was the eighth grade students of the Islamic Junior High School Al Maarif 01 Singosari Malang .The results of this research is the use of the contextual approach in learning the Arabic language in the Islamic Junior High School Al Maarif 01 Singosari Malang goes well. The learning steps that the teacher undertakes, it can be seen that the Arabic language teacher relates the material to the factual situation. From the results of the observations made by the researcher, it appears that the implementation of the learning has implemented seven elements of the contextual approach, which are construktivisme, inquiri, questioning, learning comunity, modelling, reflection and authentic assesment.